Analysis and Design of a Single‐Stage Isolated DC/AC Converter for a High‐Power‐Density Onboard AC Inverter. Issue 1 (28th September 2021) - Itoh, Kenichi; Barrera‐Cardenas, Rene; Ishigaki, Masanori; Sugiyama, Takahide; Isobe, Takanori; Tadano, Hiroshi
Abstract : This paper proposes a single‐stage DC/AC converter for the implementation of a high‐power‐density onboard AC inverter. The proposed circuit integrates a non‐isolated DC/AC converter into an isolated DC/DC converter using only simple duty control and phase‐shift modulation, which reduces the required number of semiconductor switches. Additionally, a coupling inductor and center‐tapped transformer can be shared by the two converter functions, so they can be integrated without additional circuit components. This paper describes the operating principles of the proposed converter and design solutions are extracted using multi‐objective optimization to achieve optimal performance in terms of power density and efficiency. Based on the design solution extracted through optimization, a prototype with a volume of 0.5 l was fabricated and a power density of 3.0 kW/l with an efficiency of 94.7% was achieved at a rated power of 1.5 kW. © 2021 Institute of Electrical Engineers of Japan. Published by Wiley Periodicals LLC.